2012
DOI: 10.1186/1742-6405-9-37
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determining factors associated with adherence to antiretroviral therapy (ART) in Cameroon: a systematic review and analysis of the CAMPS trial

Abstract: BackgroundThe benefits of antiretroviral therapy (ART) cannot be experienced if they are not taken as prescribed. Yet, not all causes of non-adherence are dependent on the patient. Having to pay for medication reduces adherence rates. Non- adherence has severe public health implications which must be addressed locally and globally. This paper seeks to describe the trends in adherence rates reported in Cameroon and to investigate the determinants of adherence to ART in the Cameroon Mobile Phone SMS (CAMPS) tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Similar to other studies conducted in Ethiopia [15, 34, 35], and in Africa [32, 36] the level of CD4 count during initiation of treatment have independent effect for adherence status. Non-adherence was higher among patients with a CD4 count <350 cells/mm 3 compared to their counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…Similar to other studies conducted in Ethiopia [15, 34, 35], and in Africa [32, 36] the level of CD4 count during initiation of treatment have independent effect for adherence status. Non-adherence was higher among patients with a CD4 count <350 cells/mm 3 compared to their counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…A study in Botswana showed that adherence was higher when cost was not an obstacle and poor patients were able to achieve excellent rates of adherence when they had access to free laboratory monitoring and subsidized ART [26]. Similar findings was also made in a study in Cameroon where it was observed that although ART drugs were provided free of charge, other related services were still funded by out-of-pocket payments hence a cause of non-adherence [27]. …”
Section: Treatment Of Co-infectionssupporting
confidence: 58%
“…On the other hand participants with a higher duration on ART were not willing to participate. Patient who have received ART for long periods may have developed other adherence enhancing strategies and would not be willing to include yet another [ 39 ]. They may also have developed hard-to-change medication taking habits.…”
Section: Discussionmentioning
confidence: 99%
“…They may also have developed hard-to-change medication taking habits. However, adherence to long term medication is known to wane over time and such patients require additional support [ 5 , 39 ]. For such patients it is necessary to build on the other benefits to be reaped from such a project.…”
Section: Discussionmentioning
confidence: 99%